Production of heat-stable enterotoxin by the O128 serogroup of Escherichia coli. - Reis, M H (1979)
Nine out of 11 Escherichia coli strains belonging to enteropathogenic O128 serogroup were shown to produce heat-stable enterotoxin. This property may be related to the pathogenicity of this serogroup of bacteria.